2018
DOI: 10.1007/s00425-018-3007-6
|View full text |Cite
|
Sign up to set email alerts
|

Significantly increased amino acid accumulation in a novel albino branch of the tea plant (Camellia sinensis)

Abstract: A normal tea plant with one albino branch was discovered. RNA sequencing, albinism phenotype and ultrastructural observations provided a valuable understanding of the albino mechanism in tea plants. Tea plants with a specific color (white or yellow) have been studied extensively. A normal tea plant (Camellia sinensis cv. quntizhong) with one albino branch was discovered in a local tea plantation in Huangshan, Anhui, China. The pure albino leaves on this special branch had accumulated a fairly high content of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…Deep RNA-sequence technology is a powerful tool to systemically identify key gene candidates in many plants, such as Poplar 60 , Arabidopsis 61 , Camellia sinensis 30,62,63 . To better understand the mechanism of the changes of amino acids in response to N forms and N deficiency, we examined genes encoding enzymes involved in amino acid biosynthesis and initial steps of catabolism under NO 3 − -N, EA-N, NH 4 + -N, and NH 4 + NO 3 -N and N deficiency treatments via deep RNA-seq technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep RNA-sequence technology is a powerful tool to systemically identify key gene candidates in many plants, such as Poplar 60 , Arabidopsis 61 , Camellia sinensis 30,62,63 . To better understand the mechanism of the changes of amino acids in response to N forms and N deficiency, we examined genes encoding enzymes involved in amino acid biosynthesis and initial steps of catabolism under NO 3 − -N, EA-N, NH 4 + -N, and NH 4 + NO 3 -N and N deficiency treatments via deep RNA-seq technology.…”
Section: Discussionmentioning
confidence: 99%
“…The fragments per kilobase of transcript sequence per millions of base pairs sequenced (FPKM) presented the normalized gene expression 68 . The differentially expressed genes (DEGs) among samples with different N treatments were defined using threshold as fold change ≥ 2.00 and adjusted P ≤ 0.05 according to the method 63 . For functional annotation and classification, the genes were aligned to the protein sequence database NR (http://www.…”
Section: Identification Of Differently Expressed Genes Functional Anmentioning
confidence: 99%
“…Chlorophyll analysis was carried out as described previously (Lu et al, 2019). Fresh leaves (0.1 g) were cut into small pieces and extracted overnight in 10 ml solvent (5% acetone in 95% ethanol, v/v) until the pieces became completely decolored.…”
Section: Metabolite and Phytohormone Analysismentioning
confidence: 99%
“…However, the change in leaf color during leaf senescence is later followed by leaf drop, and the leaf color in coloration mutants start with the initial stage of leaf color formation and would keep this color during leaf growth and development. Studies on leaf color mutants in different varieties of Camellia sinensis show that patterns of differentially expressed genes (DEGs) involved in chlorophyll biosynthesis or degradation, carotenoid biosynthesis or degradation, and chloroplast development affect leaf color [13,14]. Compounds related to carotenoid and chlorophyll synthesis have confirmed that the H subunit of magnesium chelatase (CHLH) and β-carotene hydroxylase (BCH) are important to the abnormal leaf color phenotype of the T. aestivum yellow-green leaf mutant [15].…”
Section: Introductionmentioning
confidence: 99%